Asianisms Regionalist Interactions and Asian Integration - Frey, Marc; Spakowski, Nicola (NUS Press, 2015)
At the core of this book is a seemingly simple question: What is Asia? the answer involves an investigation of the multifarious discursive and material constructions of Asia within the region and in the West. It reconstructs regional constellations, intersections and relations in their national, transnational and global contexts. Moving far beyond the more well-known Japanese Pan-Asianism of the first half of the twentieth century, the chapters investigate visions of Asia that have sought to provide common meanings and political projects in efforts to trace, and construct, Asia as a united and common space of interaction. By tracing the imagination of civil society actors throughout Asia, the volume leaves behind state-centered approaches to regional integration and uncovers the richness and depth of complex identities within a large and culturally heterogeneous space.